(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Dubtsova O. V. Verbal factors of an effective web course. The article studies the influence of verbal factors on the information perception while learning. The paper proves the expediency of considering verbal factors when creating a web course, as elements, playing a leading role in the perception and mastering of educational material. We have supplied general guidelines, which should be taken into account when preparing a web course as well as outlined some particular features of creating a web course in a foreign language.